Respuesta :

Answer:

The solution x = [tex]\frac{e^{3} }{3}[/tex]

Step-by-step explanation:

Step 1:-

Given [tex]log(9 x) -log 3 =3[/tex]

we have to use formula  [tex]log a-log b=log\frac{a}{b}[/tex]

[tex]log(9 x)- log 3 = log(\frac{9 x}{3} )[/tex] =[tex]3[/tex]

Again by using formula [tex]log a =b[/tex]

                                       [tex]a = e^{b}[/tex]

so [tex]\frac{9 x}{3} =e^{3}[/tex]

step 2:-

   [tex]3 x = e^{3}[/tex]

  [tex]x = \frac{e^{3} }{3}[/tex]

The solution of given problem is [tex]x=\frac{e^3}{3}[/tex]

ACCESS MORE